METHODS FOR INHIBITING ATHEROSCLEROSIS BY ADMINISTERING INHIBITOR OF PCSK9 - VIKTORIA GUSAROVA; HANS-LUDWIG SCHAEFER; WILLIAM J SASIELA; ANUSCH PEYMAN; UWE SCHWAHN (2019)
To provide methods and compositions for treatment to inhibit atherosclerotic plaque formation.SOLUTION: The invention provides a pharmaceutical composition comprising an antibody or antigen binding protein that specifically binds to PCSK9, used to reduce the number, total area, severity or destabilization increase of atherosclerotic lesions in a subject having atherosclerosis. The antibody or antigen binding protein comprises heavy and light chain CDR amino acid sequences having SEQ ID NOs:2, 3, 4, 7, 8, and 10.SELECTED DRAWING: None 【課題】アテローム硬化型プラーク形成を阻害する治療方法および組成物の提供。【解決手段】アテローム性動脈硬化症を有する対象における、アテローム硬化型病変の数、総領域、重症度、または不安定性の増加の阻害に使用するための、ＰＣＳＫ９に特異的に結合する抗体または抗原結合タンパク質を含む医薬組成物であって、前記抗体または抗原結合タンパク質は配列番号２、３、４、７、８、および１０を有する重鎖および軽鎖ＣＤＲアミノ酸配列を含む、前記医薬組成物。【選択図】なし